2019
DOI: 10.11591/ijeecs.v14.i1.pp169-177
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer neural network synchronized secured session key based encryption in wireless communication

Abstract: <p>Energy computation concept of multilayer neural network synchronized on derived transmission key based encryption system has been proposed for wireless transactions. Multilayer perceptron transmitting machines accepted same input array, which in turn generate a resultant bit and the networks were trained accordingly to form a protected variable length secret-key. For each session, different hidden layer of multilayer neural network is selected randomly and weights of hidden units of this selected hidd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The BLOSUM50 complementary rule as given in Table 3 has been obtained. The proposed binary sequence would be then passed to isosceles encryption technique [ 38 ]. The cipher matrix will be generated depending on the orientation of the key bits as given in Table 4 .…”
Section: Results Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BLOSUM50 complementary rule as given in Table 3 has been obtained. The proposed binary sequence would be then passed to isosceles encryption technique [ 38 ]. The cipher matrix will be generated depending on the orientation of the key bits as given in Table 4 .…”
Section: Results Sectionsmentioning
confidence: 99%
“…In the Telecare E-Health system, patients’ medical data has to be kept secured [ 36 , 38 , 39 ]. This is the biggest challenge for the researchers.…”
Section: Statistical Key Analysismentioning
confidence: 99%
“…Kinzel and Kanter [26] and Ruttor et al [42] described that a chance of an attack is declining if the network's weight range get increases and the assailant's calculation cost increases, as its effort increases exponentially, as users' effort becomes polynomial. Sarkar and Mandal [44], Sarkar et al [48], Sarkar et al [46], Sarkar and Mandal [45], Sarkar et al [47] proposed schemes which enhanced the security of the protocol by enhancing the synaptic depths of TPM and henceforth counteracting the attacks of the brute power of the attacker. It is found that the amount of security provided by the TPM synchronization also can be improved by introducing a large set of neurons and entries of each neuron in the hidden layers.…”
Section: Related Workmentioning
confidence: 99%
“…Gupta and Deshmukh [20] applied the protocol proposed in [8] to encrypt and decrypt the image secret sharing. Sarkar [21] applied the session key generated by the synchronization of multilayer perceptron to wireless communications. Shishniashvili et al [22] proposed a technique to use parts of the weight vector instead of the entire weight vector as the session key.…”
Section: Related Workmentioning
confidence: 99%